2021
DOI: 10.1002/jbio.202000471
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton tomography in differentiation of morphological and molecular subtypes of breast cancer: A quantitative analysis

Abstract: In this study multiphoton tomography, based on second harmonic generation (SHG), and two-photon-excited fluorescence (TPEF) was used to visualize both the extracellular matrix and tumor cells in different morphological and molecular subtypes of human breast cancer. It was shown, that quantified assessment of the SHG based imaging data has great potential to reveal differences of collagen quantity, organization and uniformity in both low-and highly-aggressive invasive breast cancers. The values of quantity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism. The second-order nonlinearity of ZnO NPs was several orders of magnitude higher than that in SHG-producing biological media, such as fibrillar collagens, which correspondingly indicated that the efficiency of nonlinear upconversion by ZnO NPs would also be significantly higher. ,, …”
Section: Resultsmentioning
confidence: 98%
“…ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism. The second-order nonlinearity of ZnO NPs was several orders of magnitude higher than that in SHG-producing biological media, such as fibrillar collagens, which correspondingly indicated that the efficiency of nonlinear upconversion by ZnO NPs would also be significantly higher. ,, …”
Section: Resultsmentioning
confidence: 98%
“…The SHG is excited by non-centrosymmetric molecules, such as collagen I in dermis [111][112][113][114] and crystallized urea structures in the stratum corneum of glabrous skin [115] can be used for their visualization in the skin. Collagen I is synthesized by fibroblasts in the dermis and, therefore, SHG microscopy can be a suitable method for fibroblast imaging.…”
Section: Healthy Skin Fibroblasts and Ecm Studied By Tpe-fmmentioning
confidence: 99%
“…They found five ‘collagen signatures’ associated with the invasion front of breast cancer cells and, by using NLOM images, were able to train a model to provide a signature score, giving a personalized approach to the prognosis and treatment of breast cancers. Similarly, Gubarkova et al used NLOM to characterize elastin fiber morphology in different forms of breast cancer, demonstrating that NLOM can be used in the morphological characterization of different states of the same disease [ 76 ].…”
Section: Imaging the Ecm Components: Past Present And Future Challengesmentioning
confidence: 99%